2019
DOI: 10.1002/polb.24897
|View full text |Cite
|
Sign up to set email alerts
|

Competition Between Interfacial Interaction and Microphase Separation in Crystallization of Filled Block Copolymers

Abstract: Understanding the effect of repulsive interaction between blocks on crystallization in block copolymers is beneficial for the design and development of sophisticated nanostructures. Dynamic Monte Carlo simulations were performed to reveal the crystallization mechanism of block copolymers containing onedimensional nanofiller under different repulsive interaction strengths between crystallizable and noncrystallizable blocks. During crystallization, crystalline morphology is determined by the competition between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Microphase separation can significantly affect the crystallization behaviors of block copolymers filled with nanofillers. It is reported that the enhancement of repulsive interaction between different blocks can promote microphase separation, which in turn leads to the local stretching of crystallizable blocks 99 . Under this condition, the crystallization process through homogeneous nucleation is promoted, as shown in Figure 7A 99 .…”
Section: Simulations Of Nanofiller‐induced Copolymer Crystallizationmentioning
confidence: 94%
See 4 more Smart Citations
“…Microphase separation can significantly affect the crystallization behaviors of block copolymers filled with nanofillers. It is reported that the enhancement of repulsive interaction between different blocks can promote microphase separation, which in turn leads to the local stretching of crystallizable blocks 99 . Under this condition, the crystallization process through homogeneous nucleation is promoted, as shown in Figure 7A 99 .…”
Section: Simulations Of Nanofiller‐induced Copolymer Crystallizationmentioning
confidence: 94%
“…97 Based on molecular simulations, similar structure has also been observed in crystalline-amorphous diblock copolymer systems filled with one-dimensional nanofiller, and the formation mechanism has also been revealed. 98,99 At the beginning of crystallization, due to the attractively interfacial interactions between Microphase separation can significantly affect the crystallization behaviors of block copolymers filled with nanofillers. It is reported that the enhancement of repulsive interaction between different blocks can promote microphase separation, which in turn leads to the local stretching of crystallizable blocks.…”
Section: Simulations Of Nanofiller-induced Copolymer Crystallizationmentioning
confidence: 99%
See 3 more Smart Citations